The press and the science: study on two media - Domínguez Gómez, Eduardo; Valle García, Carolina (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
This research is an analysis about how two generalist newspapers of Medellin (El Colombiano y El Mundo) reported the scientific news for two months. For this purpose was used a software called “Software para el análisis del tratamientoperiodístico de a información (SATPI)” (http://comunicaciones.udea.edu.co/satpi/), as well as similar researchs applied to other national and international media. This analysis found a coverage that making efforts to divulge science conceptually and visually, but does ́t approached it from a closer context to the readers. In the same way this newspapers disregard an important popularization ́s target: reflect the social dimension of science and promote a dialogue between technoscience and general public.